SCREENING LIPASE FROM ENDOPHYTIC BACTERIA FROM STEAM OF (Costus speciosus (J.Koenig) Sm) AND OPTIMUM WORKING CONDITION - Asjayani Kurnia Sari; Winni Astuti; Djihan Ryn Pratiwi (Jurusan Kimia FMIPA UNMUL, 2020)
Endophytic bacteria are bacteria that live in plant tissues such as the roots, leaves, and stems of plants. This research was conducted to screen lipase-producing endophytic bacteria from Pacing stem (Costus speciosus (J.Koenig) Sm.) and determine the optimum working conditions. Screening of lipase-producing bacteria on nutrient agar media containing olive oil and Rhodamine B showed that one isolate was able to produce lipase. The crude lipase extract produced from endophytic bacteria worked optimally at a pH of 7, the temperature of 40â„ƒ, and a substrate concentration of 2%. Keywords : Costus speciosus (J.Koenig) Sm., Endophytic bacteria, Lipase, Optimum Activity